The discovery of dark oxygen and its significance: Impacts on the Earth’s environment, deep-sea ecosystems, and energy utilization - Shangguan, Liren (Geographical Research Bulletin, 2025)
The discovery of dark oxygen can bring innovations in multiple fields, including reconsidering the Earth’s oxygen supply mechanisms, a deeper understanding of deep-sea ecosystems, and exploring new energy sources. This phenomenon is believed to occur when polymetallic nodules electrolyze seawater, generating oxygen, and it is suggested that it may play a crucial role in deep-sea material cycles and biological activities. Furthermore, applying this principle could pave the way for its utilization as a renewable energy source. However, many aspects of its generation mechanism and its impact on deep-sea ecosystems remain unknown. In particular, careful research and the development of environmentally friendly technologies are necessary to assess the potential effects of deep-sea mining on dark oxygen supply and marine ecosystems.